Comparative organizational network analysis considering formal power-based networks and organizational hierarchies - Ramos, Valentina (2022)
Comparative organizational network analysis makes it possible to identify the similarities and differences between organizations according to the content of their networks. This research is a comparative study of organizational networks based on formal power. To accomplish this goal, networks were developed in three organizations from different sectors with workers distributed in high, middle and operational levels in the organizational hierarchy. For the study, 100% of the workers within the identified networks were included. The results indicated that, considering centrality and connectivity network indices, there were no statistically significant differences between organizations according to formal power network behavior. However, we obtained statistically significant differences in terms connectivity and centrality considering the workers’ hierarchy. The representative nodes of high and middle hierarchical levels had higher indices of connectivity and centrality than the nodes representative of the operational level. This study makes it possible to identify the formal roles within networks based on legitimate power, which can serve as a basis for decision-making processes and resource allocations, for the strategic use of the networks created.